Предмет: Алгебра,
автор: kretipesh1
СРОЧНО НУЖНА ПОМОЩЬ!!ПОМОГИТЕ!!
Приложения:
Ответы
Автор ответа:
0
f(x)' = -(x²+7) - 2x(2-x) = -x² -7 -4x+2x² = x² -4x -7
(x² +7)² (x² +7)² (x² +7)²
x² -4x -7 >0
(x² +7)²
(x² +7)² >0 при любом х.
x² -4x-7>0
x²-4x-7=0
D=16+28=44
x₁ = 4-√44 = 4 - 2√11 = 2 - √11
2 2
x₂ = 2 + √11
+ - +
------------ 2-√11 ------------- 2+√11 -------------
\\\\\\ \\\\\\\\
x∈(-∞; 2-√11)U(2+√11; +∞)
(x² +7)² (x² +7)² (x² +7)²
x² -4x -7 >0
(x² +7)²
(x² +7)² >0 при любом х.
x² -4x-7>0
x²-4x-7=0
D=16+28=44
x₁ = 4-√44 = 4 - 2√11 = 2 - √11
2 2
x₂ = 2 + √11
+ - +
------------ 2-√11 ------------- 2+√11 -------------
\\\\\\ \\\\\\\\
x∈(-∞; 2-√11)U(2+√11; +∞)
Похожие вопросы
Предмет: Қазақ тiлi,
автор: Аноним
Предмет: Математика,
автор: lastok0999
Предмет: Қазақ тiлi,
автор: elizabeth9855
Предмет: Математика,
автор: Deansk87